Laboratory practices applied to the development of an independent editorial project - Sanches, Miguel (Convergences - Journal of Research and Arts Education, 2020)
Technological advances and overwhelming presence of digital tools in our day-to-day lives, necessarily have an impact on the practice of design, where we can increasingly find preference for the instantaneous and ephemeral communication channels, in detriment of manual or conventional reproduction techniques. Concerning teaching practices, and particularly in the areas of design, there is an increasing hunger for training based on digital tools, where the student is faced with the need to present an answer to a certain problem, using almost exclusively known graphic software’s. This article aims to demonstrate, through a practical example, how students can be encouraged to look for graphic solutions through laboratory practices, using analogue tools, where the results presented were often shaped by this practice and not just a standard solution proposed by a software. The example presented in this paper is based on the extracurricular editorial project, i.E. Magazine, that students of the Degree in Design and Graphic Arts Technology (DGAT) of the Polytechnic Institute of Tomar (PIT) have developed in recent years, with the objective of contributing to learning outside the classroom, encouraging the use of equipment and materials provided by the printing labs of this institution. This magazine is owned by DGAT students and has served as a platform for exploring the PIT printing laboratories, but also as a way for students to express themselves, without the commitment to respond to an exercise, program or problem placed in the classroom. The students that embrace this project are responsible for the choice of all the written content, for the external request for articles, for the collection or production of images and illustrations, for the design and layout, for the choice of materials and means of production, for the printing and finishing and for the distribution. In the first part of this paper, we pretend to address mainly issues related to independent publication – the term is used here, not as a closed and definitive characterization, but only in order to distinguish an area of editing, apart from the traditional means of creation, production, dissemination and distribution – in order to understand its context and recognize how this kind of light-hearted edition, without resources and, almost always, without a commercial objective can influence the choice of tools, materials and resources, as a mean to produce a graphic object. In a second part we will try to explore how the experimentation and exploration of traditional production techniques in a workshop context can lead the student to unexpected results, often imposed by technical, laboratory or time-based limitations related to the use of almost artisanal production techniques. For a third part of this paper, we will present the approaches taken in the production of the sixth edition of the i.E. Magazine that usually starts with a set of limitations presented by the editor and that the students plan to solve as they explore the different solutions that laboratory practices allow. For each of the issues of this magazine it is essential to use the laboratory spaces offered by PIT, making the student conscious of a much wider reality that those they can found on the computer, on digital tools, or even within a traditional classroom. With this article we hope to accomplish that having access to other, more experimental learning methods, allows amplifying the student's creative vision and makes it possible to improve the learning processes. The collaborative methodologies used in the context of a workshop are relevant in the practices of graphic and editorial design, placing the designer also as an author, collaborator and producer, capable of dictating high-value content and practical solutions. The review of creative processes and tools used, transforms the designer as an author, into a more informed and conscious professional, allowing the approach to traditional technologies and contributing to their recognition and applicability in a professional context.